Pengaruh Literasi Ekonomi terhadap Perilaku Pengelolaan Keuangan Mahasiswa Jurusan Pendidikan Ekonomi FKIP UHO - Yuniyarti Ahiri; Jafar Ahiri; Muni Nia; Harjun Harjun; Muhammad Juwantho Lewa; Wahyu Muh. Syata; Ilhamurrahman M Hubaib (Indo Publishing, 2026)
This study aims to analyze the effect of economic literacy on financial management behavior among students of the Economics Education Department, Faculty of Teacher Training and Education (FKIP), Halu Oleo University (UHO). This quantitative research employed a simple linear regression design with a proportional stratified random sampling technique involving 80 students as the research sample from a population of 111 students. Data were collected using the Economic Literacy Scale based on Sina (2012) and the Financial Management Behavior Scale adapted from Dew and Xiao (2011). Prerequisite assumption tests confirmed that data were normally distributed (Asymp. Sig. = 0.147 > 0.05), had a significant linear relationship (Sig. Linearity = 0.000 < 0.05), and were free from heteroscedasticity (Sig. Glejser = 0.228 > 0.05). The results of simple linear regression showed that economic literacy had a positive and significant effect on financial management behavior (B = 0.601, β = 0.632, t = 7.215, p = 0.000), indicating that higher students' economic literacy was associated with better financial management behavior.